Implementasi Media Pembelajaran Robokids Berbasis STEAM Untuk Meningkatkan Minat Belajar Dan Prestasi Belajar Siswa Sekolah Dasar - Irfan Saninur Azis; Muniroh Munawar; Sukamto (Elementary Teacher Education Program, Majalengka University, 2023)
The background of this research is the lack of interest in learning and student learning achievement, the lack of use of STEAM-based learning media in learning so that learning is less interesting so that it affects student learning interest. This study aims to describe how interest in learning and learning achievement of elementary school students is influenced by STEAM-based robokid learning media. One group pretest-posttest design is used in this type of quantitative descriptive research. In this study, questionnaires, interviews, and observations were used to collect data. In this research using data analysis techniques in the form of Paired samples t-test and N-gain score test. In the paired samples t-test, the results of data analysis of learning interest and learning achievement show sig. (2-tailed) 0.000 <0.05. Interest in learning gets an average N-Gain Score of 0.7014 on the N-Gain Score test, while learning achievement gets an average N-Gain Score of 0.4029. It was concluded that STEAM-based robokid learning media can improve the learning achievement of elementary and high school students. So that robokids learning media can be used by teachers in learning.